Tea consumption affects the absorption of levothyroxine - Lai, Ying-Wen; Huang, Shih-Ming (Frontiers in Endocrinology, 2022)
Levothyroxine (LT4) is a convenient treatment for hypothyroidism. Coffee, however, prevents the body from efficaciously absorbing LT4. It is unknown whether the intake of tea interferes with LT4 absorption. Thirty-seven hypothyroidism patients with the following types of consumption were recruited: 1) only tea, 2) tea and coffee, and 3) only coffee. The concentrations of thyroid-stimulating hormone (TSH), triiodothyronine (T3), and thyroxine (T4) were recorded before and 3 months after changing the consumption. The patients had reductions in the concentration of TSH to varying degrees after 3 months (p < 0.001 or p < 0.05). The natural logarithms of the differences between the concentrations of TSH before and after the change in the consumption (Δln-TSH) of tea and coffee, only coffee, and only tea were 1.94, 2.00, and 2.18, respectively. Long-term consumption of tea, like coffee, interfered with the absorption of LT4. We believe that avoiding tea when taking LT4 will reduce malabsorption.